Taxi to Tobruk - Havard, Rene, 1923- (Collins, 1962)
A novel about the experiences of a group of Frenchmen led by a British Officer assigned to the Long Range Desert Group whose mission was to blow up Rommel's petrol dumps in Tobruk during World War II.